FEEDZ - Datu Unoi, Datu Mohd Azmeer; Awangku Amir Azam, Dayangku Amira Edzana; Edward, Ervin; Herman, Francis Finan; Darus, Nur Zahirah (2015)
FEEDZ is a manufacturing company in producing simple and systematic eco-friendly tools and equipment that are creatively invented to assist humankind in their daily life. Using the tagline "Creative Innovation without Limits", we wanted people to be aware that we are taking creative innovation highly important. Our main building and factory is located at the same place which is at , KKIP Selatan, 88450 Sepanggar, Kota Kinabalu, Sabah. Our very first product is "Notice Me" parking indicator that functions as an indicator to assist car users in finding vacant or available parking spaces to park their cars. The benefit offer of the product is; reducing time taken for car users to look for available parking space rather than going around just trying to find one and wasting gas. We choose Kota Kinabalu area as our first distribution location as Sabah is falling behind in terms of parking systems unlike in peninsular Malaysia and Sarawak, where most of the shopping malls at there are using high-tech parking indicators. Besides, the population in Sabah is getting bigger especially in Kota Kinabalu area where most of the civilians are using their personal cars as daily transportations which causes massive traffic jammed or crowded parking spaces making it harder to find available parking spaces. Thus, referring to the current situation in Sabah especially in Kota Kinabalu, we believe that the invention of "Notice Me" parking indicator will be able to solve the problems and we, FEEDZ wilI take this as an opportunity and challenge to make it big and achieve our goals.